Flexibly weighted integration of tactile reference frames. (April 2015) - Badde, Stephanie; Röder, Brigitte; Heed, Tobias
Abstract: To estimate the location of a tactile stimulus, the brain seems to integrate different types of spatial information such as skin-based, anatomical coordinates and external, spatiotopic coordinates. The aim of the present study was to test whether the use of these coordinates is fixed, or whether they are weighted according to the task context. Participants made judgments about two tactile stimuli with different vibration characteristics, one applied to each hand. First, they always performed temporal order judgments (TOJ) of the tactile stimuli with respect to the stimulated hands that were either crossed or uncrossed. The resulting crossing effect, that is, impaired performance in crossed compared to uncrossed conditions, was used as a measure of reference frame weighting and was compared across conditions. Second, in dual judgment conditions participants subsequently made judgments about the stimulus vibration characteristics, either with respect to spatial location or with respect to temporal order. Responses in the spatial secondary task either accented anatomical (Experiment 1) or external (Experiment 2) coding. A TOJ crossing effect emerged in all conditions, and secondary tasks did not affect primary task performance in the uncrossed posture. Yet, the spatial secondary task resulted in improved crossed hands performance in the primary task, but only if the secondary judgment stressed the anatomical reference frame (Experiment 1), rather than the external reference frames (Experiment 2). Like the anatomically coded spatial secondary task, the temporal secondary task improved crossed hand performance of the primary task. The differential influence of the varying secondary tasks implies that integration weights assigned to the anatomical and external reference frames are not fixed. Rather, they are flexibly adjusted to the context, presumably through top-down modulation. Highlights: An irrelevant extra tactile task affected spatial conflict in a primary tactile task. Spatial conflict effects were reduced when extra task stressed anatomical coordinates. Weighting of tactile reference frames is top-down modulated according to task context.